Intermittent Blood Glucose Examination In The Community Of Rt 25 Sawah Lebar Urban Village, Ratu Agung Sub-District,Bengkulu City, Bengkulu Province - Buchari, Widya; Elviyanti , Desi; Syafrisman , Henda; Kurniawan , Nelson; Indryanni , Dwi Debby; Sudiyanto, Sudiyanto (Jurnal Pengabdian Mandiri, 2025)
The importance of community service activities is to help the community, especially people from the lower middle class, to carry out supporting examinations for cardiovascular diseases which are often suffered by the community. The aim of this community service activity is to find out the results of blood glucose examinations in the community at RT 25, Sawah Lebar Village, Ratu Agung District. Bengkulu City. Blood sugar or blood glucose is sugar found in the blood and comes from the formation of carbohydrates from food and is stored as glycogen in the liver and skeletal muscles. The insulin hormone is a hormone that affects blood sugar levels. The reference value for blood glucose levels in plasma is 70-110 mg/dl, glucose 2 hours post prandial (after glucose administration) ≤140 mg/dl/2 hours, and immediate blood glucose ≤110 mg/dl. The method is carried out by taking a brief history and checking blood sugar levels with a device. After the examination, it was found that of the 32 people examined, 1 of them had high blood sugar levels, and the other 31 people were normal. It is best to check blood sugar levels on an ongoing basis to prevent non-communicable diseases as early as possible, especially for people who have the potential to experience this disease and for people who already suffer from Diabetes Mellitus, they can control their blood sugar levels so that they remain within reasonable limits so that complaints of signs and symptoms do not occur. which is undesirable.